2011
DOI: 10.1523/jneurosci.0501-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Disrupts Theta Modulation of Gamma in a Computer Model of Hippocampus

Abstract: Abnormalities in oscillations have been suggested to play a role in schizophrenia. We studied theta-modulated gamma oscillations in a computer model of hippocampal CA3 in vivo with and without simulated application of ketamine, an NMDA receptor antagonist and psychotomimetic. Networks of 1200 multi-compartment neurons (pyramidal, basket and oriens-lacunosum moleculare, OLM, cells) generated theta and gamma oscillations from intrinsic network dynamics: basket cells primarily generated gamma and amplified theta,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
157
2
10

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(175 citation statements)
references
References 71 publications
6
157
2
10
Order By: Relevance
“…13). For instance, PAC could stem from pulses of inhibition paced at the slower frequency and targeted at the generators of the faster oscillation Neymotin et al, 2011;Tort et al, 2007;Wulff et al, 2009). One concept on the mechanisms underlying HFOs postulates that rhythmic activity is generated within a plexus of electrically coupled axons (Traub , 2002, 2003).…”
Section: Possible Cellular and Network Mechanisms Underlying Hfos Andmentioning
confidence: 99%
“…13). For instance, PAC could stem from pulses of inhibition paced at the slower frequency and targeted at the generators of the faster oscillation Neymotin et al, 2011;Tort et al, 2007;Wulff et al, 2009). One concept on the mechanisms underlying HFOs postulates that rhythmic activity is generated within a plexus of electrically coupled axons (Traub , 2002, 2003).…”
Section: Possible Cellular and Network Mechanisms Underlying Hfos Andmentioning
confidence: 99%
“…The latency (a) and the duration (b) of loss of righting reflex were recorded. All values are expressed as the mean ± SEM are mainly attributed to the NMDAR blockade, as it is a prominent feature of most NMDAR antagonist compounds (Nakao et al 2003;Neymotin et al 2011;Thomson et al 1985;Vollenweider and Geyer 2001). Betaine might counteract the psychotomimetic effects of ketamine through modulating the NMDAR glycine binding site since the beneficial effect of betaine in the NORT was significantly attenuated by 7-chlorokynurenic acid (7-CTKA), an antagonist for the NMDAR glycine binding site (Supplement 1).…”
Section: Discussionmentioning
confidence: 99%
“…Several drugs that effectively either block or antagonize NMDAR activity, such as the competitive NMDAR antagonists CGP 37849 and CGP 40116 (Papp and Moryl 1994), the noncompetitive, nonsubunit selective NMDAR antagonist MK-801 (Autry et al 2011;Lima-Ojeda et al 2013;Maeng et al 2008), and the NR2B selective antagonist RO-25-6981 (Lima-Ojeda et al 2013;Maeng et al 2008), have repeatedly and consistently been shown to have antidepressant-like properties in rodent models. NMDAR blockade is also the main contributor of the psychotomimetic effects of ketamine, as most NMDAR antagonist compounds have the same properties (Nakao et al 2003;Neymotin et al 2011;Thomson et al 1985;Vollenweider and Geyer 2001). On the other hand, enhancement of NMDAR function, via activation of glycine binding site or modulation of metabotropic glutamate receptors, represents a promising approach to reverse psychotomimetic effects of ketamine (Chan et al 2008;Krystal et al 2005;Roberts et al 2010;Yang et al 2010) or other NMDAR antagonists (Kanahara et al 2008;Kawaura et al 2015;Lipina et al 2005;Santini et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Neymotin and colleagues [64] used a computer model of hippocampal CA3 to investigate the effect of the application of simulated ketamine. Ketamine administration disrupted theta-gamma coupling in the simulation, apparently due to its antagonistic effect on NMDA receptors on orienslacunosum moleculare cells (OLM); normal coupling was restored via injection of a continuous, depolarizing current into these OLM cells, suggesting a potential intervention for treating deficits in WM and other cognitive processes in PSZ.…”
Section: Theta-gamma Coupling In People With Schizophreniamentioning
confidence: 99%